Corneal nerve healing after in situ laser nerve transection - Sarkar, Joy (PLoS One, 2019)
PURPOSE: We have previously reported that lamellar dissection of the cornea transects stromal nerves, and that regenerating neurites form a dense net along the surgical plane. In these experiments, we have disrupted the stromal nerve trunks in situ, without incising the cornea, to determine the regeneration events in the absence of a surgical plane. METHODS: Thy1-YFP mice were anesthetized and in vivo images of the corneal nerves were obtained with a wide-field stereofluorescent microscope. A far infrared XYRCOS Laser attached to 20X objective of an upright microscope was used to perform in situ transection of the stromal nerves. 3 types of laser transections were performed (n = 5/group): (i) point transection (a single cut); (ii) segmental transection (two cuts enclosing a segment of nerve trunk); and (iii) annular transection (cuts on all nerve trunks crossing the perimeter of a 0.8 mm diameter circular area centered on the corneal apex). Mice were imaged sequentially for 4 weeks thereafter to assess nerve degeneration (disappearance or weakening of original fluorescence intensity) or regeneration (appearance of new fluorescent fronds). Beta-3-tubulin immunostaining was performed on corneal whole-mounts to demonstrate nerve disruption. RESULTS: The pattern of stromal nerves in corneas of the same mouse and in corneas of littermates was dissimilar. Two distinct patterns were observed, often within the same cornea: (i) interconnected trunks that spanned limbus to limbus; or (ii) dichotomously branching trunks that terminate at the corneal apex. Point transections did not cause degeneration of proximal or distal segment in interconnected trunks, but resulted in degeneration of distal segment of branching trunks. In segmental transections, the nerve segment enclosed within the two laser cuts degenerated. Lack of beta-3 tubulin staining at transection site confirmed nerve transection. In interconnected trunks, at 4 weeks, a hyperfluorescent plaque filled the gap created by the transection. In annular transections, some nerve trunks degenerated, while others regained or retained fluorescence. CONCLUSIONS: Interconnected stromal nerves in murine corneas do not degenerate after in situ point transection and show evidence of healing at the site of disruption. Presence or absence of a surgical plane influences corneal nerve regeneration after transection.